2020
DOI: 10.1002/cmdc.202000147
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Novel Pyridine‐Carboxylates as Small‐Molecule Inhibitors of Human Aspartate/Asparagine‐β‐Hydroxylase

Abstract: The human 2‐oxoglutarate (2OG)‐dependent oxygenase aspartate/asparagine‐β‐hydroxylase (AspH) is a potential medicinal chemistry target for anticancer therapy. AspH is present on the cell surface of invasive cancer cells and accepts epidermal growth factor‐like domain (EGFD) substrates with a noncanonical (i. e., Cys 1–2, 3–4, 5–6) disulfide pattern. We report a concise synthesis of C‐3‐substituted derivatives of pyridine‐2,4‐dicarboxylic acid (2,4‐PDCA) as 2OG competitors for use in SAR studies on AspH inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(31 citation statements)
references
References 73 publications
1
30
0
Order By: Relevance
“…2OG-competition for binding the AspH active site ( e.g. N -oxalylglycine, 28 , 36 , 86 pyridine-2,3-dicarboxylic acid 21. , 87 ) and Fe(II)-chelation ( e.g.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2OG-competition for binding the AspH active site ( e.g. N -oxalylglycine, 28 , 36 , 86 pyridine-2,3-dicarboxylic acid 21. , 87 ) and Fe(II)-chelation ( e.g.…”
Section: Discussionmentioning
confidence: 99%
“…11 , 12 Studies on naturally occurring mutations of human AspH presumably resulting in inactive AspH (Traboulsi syndrome) 13 , 14 , 15 , 16 and animal models 8 , 17 , 18 suggest that AspH might affect cell motility through the notch signalling pathway. Despite the combined evidence suggesting that AspH is a promising medicinal chemistry target for the development of small-molecule-based cancer therapeutics, comparatively few AspH inhibition studies using small-molecules are reported, with most of these relying either on the use of likely non-selective 19 , 20 or partially selective 21 small-molecules or on the use of l -ascorbic acid (LAA)-derived small-molecules. 18 , 22 , 23 , 24 This likely reflects the historic lack of simple and reliable assays to monitor recombinant human AspH activity in vitro .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nortrilobolide and related compounds are reported to be potent cytotoxic agents with subnanomolar sarco/endoplasmic reticulum calcium ATPase (SERCA) inhibition [93]. Recently, a family of potent pyridine dicarboxylates have also been published [65] utilizing a mass spectrometry-based inhibition assay [94]. These compounds are related to known iron-dependent dioxygenase inhibitors 2,3-pyridine dicarboxylate, 2,4-pyridine dicarboxylate and 2.6-pyridine dicarboxylate.…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%
“…The synthesized pyridine dicarboxylates were assayed for activity against a range of other enzymes, to include PHD2, FIH, and lysine-specific demethylase 4E (KDM4E) in addition to ASPH, with varying degrees of selectivity. However, while cell-based activities have not been evaluated, the dicarboxylate nature of the compounds may be useful for cell surface ASPH inhibitors that may not have cell penetrating activity [94].…”
Section: Small Molecule Inhibitorsmentioning
confidence: 99%